598 Reversal of epigenetic silencing of cGAS and STING in melanoma enhances the activity of tumor infiltrating lymphocytes. (10th December 2020) - Falahat, Rana; Mulé, James; Berglund, Anders; Villarroel, Patricio Perez-; Putney, Ryan; Pilon-Thomas, Shari; Barber, Glen
Abstract : Background: It is becoming more evident that STING activity in tumor cells can have a functional role in mediating antitumor immune responses. We have recently shown that activation of STING signaling in human melanoma cell lines enhances their antigenicity and susceptibility to lysis by human melanoma tumor infiltrating lymphocytes (TIL) through the augmentation of MHC class I molecules. 1 However, the frequent impairment of this pathway through loss of cGAS and/or STING expression in melanoma cell lines limits their antigen presentation and subsequently their sensitivity to cytotoxic T cell mediated killing. In this study, we asked if this suppression is, in part, epigenetically regulated and if it is indeed a driver of melanoma resistance to T cell-based immunotherapies. Methods: To determine the role of DNA methylation in melanoma STING and cGAS silencing, we performed genome-wide DNA methylation profiling across a panel of 16 human melanoma cell lines. We subjected melanoma cell lines that indicated STING and/or cGAS promoter hypermethylation to treatment with 5-aza-2'-deoxycytidine (5AZADC) and evaluated their protein expression by immunoblot. We next assessed phosphorylation of IRF3 and induction of IFN-β and CXCL10 in 5AZADC-treated melanoma cells following their stimulation with dsDNA or 2'3'-cGAMP. We also co-cultured 5AZADC-pretreated melanoma cell lines with their HLA-matched human melanoma TIL in the presence or absence of dsDNA or 2'3'-cGAMP and assessed TIL production of IFN-γ. Results: Using whole genome methylation profiling, we identified a distinct correlation between promoter hypermethylation and loss of STING and cGAS expression in human melanoma cell lines. Reconstitution of STING and cGAS expression through DNA demethylation reinstated functional STING signaling in at least half of the examined cell lines as indicated by STING-dependent phosphorylation of IRF3, induction of CXCL10 (~300 pg/ml, P < 0.0001) and IFN-β (~900 pg/ml, P < 0.0001) and upregulation of MHC class I. We also observed up to a 8-fold increase in TIL production of IFN-γ in co-culture studies using 5AZADC-pretreated melanoma cells compared to untreated controls in the presence of dsDNA or 2'3'-cGAMP (~2, 000 pg/ml, P < 0.001). Conclusions: We provide evidence that methylation silencing of cGAS and STING is not only a notable mechanism of STING signaling dysfunction in melanoma, but also plays a role in tumor antigen presentation and recognition by TIL. Collectively, these observations argue that targeting epigenetic loss of STING signaling in melanomas should be considered as a strategy to improve the efficacy of clinical interventions using T cell-based immunotherapies. Acknowledgements: Funding: NCI P50 CA168536, Cindy and Jon Gruden Fund, Chris Sullivan Fund, V Foundation, Dr. Miriam and Sheldon G. Adelson Medical Research Foundation. Reference: Falahat R, Perez-Villarroel P, Mailloux AW, Zhu G, Pilon-Thomas S, Barber GN, Mulé JJ. STING signaling in melanoma cells shapes antigenicity and can promote antitumor T-cell activity. Cancer Immunology Research 2019; 7(11):1837–48.